The prediction of landslide slip surface based on the correlation between relative density and dynamic cone penetration test - Nor Shahidah Mohd Nazer; Ahmed Mohamed Kotb Shahin; Azlan Shah Nerwan Shah; Goh, Thian Lai; Mohd Rozi Umor; Mohamad Anuri Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2023)
Relative density is one of the most important properties indicating the strength and state of compaction of the soil. The dynamic cone penetration test is considered one of the fastest field tests for evaluating the relative strength of soil layers, including density. In this study, an attempt is made to correlate the relative density of the landslide soil with the dynamic cone penetration results. The aim of this study was to delineate the boundary between moving and in-situ soil for the prediction of slip surfaces and finally to conceptualise the underlying mechanism behind the initiation of a landslide. The results of the penetration tests give an increasing index of 1.9 - 2.4 cm/blow, 2.8 - 3 cm/ blow and 3.2 cm/blow for the upper, middle and lower parts (toe), respectively. Using the correlation equation, the calculated relative density in the field was found to agree well with the relative density measured in the laboratory with a standard deviation of ±1.5%. The relationship between the relative density and the penetration index shows an inverse relationship where the resistance of the soil to dynamic penetration increases as the relative density of the soil increases, thus decreasing the penetration index. This result can be used to accurately conceptualize the mechanism behind a landslide using a simple and rapid field device.